Formation of linguistic and speech competence of primary school students (Pedagogy of Higher and Secondary Education, 2012)
Diduk-Stup'yak H. I. Formation of linguistic and speech competence of primary school students.Тhe article deas with the basic school students’ speech training peculiarities during the process of application of the innovative linguistic and methodical technology «The polytypic approaches interaction for  learning Ukrainian language». The actuality, the tasks of the research and methodical basis educational actions confrontation in four types of speech activity are found out. Some definitions for «approach» and the own interpretation of this term are indicated; the system of the word combination poetic studying at the fifth year in the way of the combination of such approaches as communicative and active, personalityoriented, social and cultural, text centered and competent.
Keywords: speech training; interaction; linguistic and methodical technology; approach; word combination poetic studying